Speculating a swarm-based symbiotic architecture in the era of Mothering Nature (ARSNET, 2025)
This experimental design study explores forms of adaptive architecture that reflect the symbiotic connection between humans and nature. Responding to the growing ecological between human and nature, this paper speculates how architecture can be an entity that coexists and co-evolves with nature. Instead of positioning architecture as a static entity, this symbiotic architecture introduces the conceptual figure of Homo botanicus as human species that grows and regenerates nature as its imperative, initiating the era of Mothering Nature. The study starts by investigating the adaptive strategy of plants that grow symbiotically within their natural biomes. The biological growth mechanism of plants across three biomes—tropical, savannah, and coastal wetland—was examined, mapped, and translated into computational scripts. Such scripts serve as the basis of H. botanicus' living world: Verdantia, Aridstepia, and Aqualandis, exhibiting a close intertwine between species and their living system. The design envisions an architecture as a symbiont that regenerates nature together with its natural ecosystem. This study demonstrates the understanding of architecture not as exploitative but co-evolving, growing with nature's innate logic and contributing to its ecological resilience.